Perspectives of Local Government Amalgamations in a Transition Society: The Case of Estonia - Sootla, Georg; Kalev, Leif; Kattai, Kersten (Studies of Transition States and Societies, 2009)
This article analyses the general institutional preconditions and restraints of a successful local government amalgamation policy in Estonia from a Central and Eastern European perspective. We start by re-examining and re-synthesising the dynamics of capacity-scale problems during the post-communist transition. On this basis, we analyse the patterns and models of local governance and amalgamations in the sparsely populated countries with already large municipalities, developing the possibilities and barriers to achieve economy of scale and economy of scope. The article addresses key factors of local governance and amalgamations, first of all their relations vis-à-vis the citizens and the civil society. The vicious circle of a clan pattern of local government and citizen estrangement can be broken when the existing practice of municipality amalgamation will be changed. The mediating role of the central government or citizens’ peak organisations must become central in the amalgamation process, because they can neutralise the traditional corporatist values of local elites at negotiations and promote the new structural profile of a municipality based on the values of democratic governance.